Religious Moderation in Educational Practices in Islamic Senior High School - Elena kamilia Awawina; Machnunah Ani Zulfah (LPPM Universitas KH. A. Wahab Hasbullah, 2023)
This research began with the researcher's interest in the application of religious moderation values in the Islamic Senior High School Darun Najah Ngijo Karangploso Malang environment. Therefore, the problems examined in writing the final assignment are: 1). How to implement the values of religious moderation in the Islamic Senior High School Darun Najah Ngijo Karangploso Malang 2.) How to implement the values of religious moderation in the Madrasah Aliyah Darun Najah Ngijo Karangploso Malang environment. 3). How to evaluate the implementation of religious moderation values within Senior High School Darun Najah. To answer this problem, researchers used qualitative research methods to obtain data. Researchers used data collection techniques with observation, interviews, and documentation as complementary research aids. Religious moderation as a perspective can be a solution for mutual openness and mutual acceptance of differences between regions, ethnicities, races, and cultures as well as religion, one of which is through additional learning of Ahlussunnah Waljamaah (ASWAJA) education in its subjects. The results of this research can conclude that the implementation of religious moderation values at Islamic Senior High School Darun Najah has been running and has been implemented smoothly and well because many factors support students to better understand and apply religious moderation in their daily lives in the environment of school.